2015
DOI: 10.1111/capa.12118
|View full text |Cite
|
Sign up to set email alerts
|

Local governance and the local political career in Canada: A sample dataset

Abstract: This research note introduces and describes a new dataset of political actors from the city of Kitchener, Ontario. The dataset is comprised of 348 complete political careers, across four local institutions, from 1912 to the present. This research note aims to show that large‐scale databases of local political actors can contribute to our understanding of (a) local political careers, (b) the dynamics of formal and informal local institutions, and (c) the nature and boundaries of local multilevel governance. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Research activity in the area of local electoral politics has increased significantly in recent years (Breux et al, 2017; Lucas, 2015; McGregor et al, 2016; Siemiatycki, 2011), with much academic effort focused on the representation of women or racial minorities. This work has broadly concluded that women and/or racial minorities are underrepresented in local government, as they are at other orders of government (Bird, 2015; Bird et al, 2016; Breux et al, 2018; McGregor et al, 2016; Spicer et al, 2017; Tolley, 2011).…”
mentioning
confidence: 99%
“…Research activity in the area of local electoral politics has increased significantly in recent years (Breux et al, 2017; Lucas, 2015; McGregor et al, 2016; Siemiatycki, 2011), with much academic effort focused on the representation of women or racial minorities. This work has broadly concluded that women and/or racial minorities are underrepresented in local government, as they are at other orders of government (Bird, 2015; Bird et al, 2016; Breux et al, 2018; McGregor et al, 2016; Spicer et al, 2017; Tolley, 2011).…”
mentioning
confidence: 99%